The Properties of Hemp Crocheted Fabric Product Mixed with Stainless Steel Yarn for Electromagnetic Shielding - พุทธรัตน์, นคเรศ; ชลสาคร, ผู้ช่วยศาสตราจารย์ ดร.สาคร; บุญโญภาส, รองศาสตราจารย์สุทัศนีย์ (Journal of Food Health and Bioenvironmental Science, 2017)
The objectives of this research were to study the efficacy of electromagnetic radiation shielding and the properties of crochet knitted fabric made from hemp yarn and stainless steel yarn to re-design and develop fabric products, and to observe customers’ opinions towards the fabric products. The materials in this study included hemp yarn, stainless steel yarn, and crochet hooks. The methods used in this study were, firstly, studying two ratios in which the two yarns were knitted together in the ratios 1:1 and 1:2 of hemp yarn and stainless steel yarn respectively. Two Knitting patterns were studied: the first pattern consisted of the two yarns knitted together all the way through the length of the fabric and the second pattern consisted of repetitions of two rows of knitted hemp yarn followed by a row of knitted stainless steel yarn. Crochet techniques to create crochet knitted fabric made of hemp yarn and stainless steel yarn types were: single, half double, triple, double and triple crochets. The results indicated that the above ratios, patterns and the knitting techniques of hemp yarn with stainless steel yarn affected the electromagnetic wave protection efficiency and its physical properties (p<0.05). The usability of this fabric in both width and weft knitting decreased 5%. The ability to shield against electromagnetic radiation of the fabric decreases after the fabric was washed 1, 3, 5 and 10 times. The customers’ satisfaction towards the 4 patterns of the crochet knitted fabric characteristic was the highest level.